2022
DOI: 10.1371/journal.pone.0269452
|View full text |Cite
|
Sign up to set email alerts
|

How do high-performance work systems affect work fatigue: The mediating effect of job responsibility and role overload

Abstract: Work fatigue refers to physical, mental, and emotional exhaustion, resulting in the inability to work. Hitherto research indicate a close relationship between high-performance work systems and work fatigue, and there may be a double-edged sword effect of high-performance work systems on work fatigue. However, a comprehensive theoretical framework has not been developed to understand the relationship between them. Based on the challenge-hindrance stress model, this study employs role overload and job responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A study by Yurko et al [ 15 ] concluded that a higher mental workload due to increased fatigue could lead to decreased job performance and even surgeon human errors. The effects of fatigue on the job performance of surgeons and the mediating role of job responsibility and role overload have been investigated by Jiandong et al The results of their study approve the effect of increased fatigue on the performance of surgeons and the amplification of this effect with increasing job responsibility and role overload [ 52 ]. Also in another study, Fan et al [ 32 ] stated that mental workload with increased fatigue can lead to a decrease in job performance, and fatigue mediates the relationship between mental workload and job performance.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yurko et al [ 15 ] concluded that a higher mental workload due to increased fatigue could lead to decreased job performance and even surgeon human errors. The effects of fatigue on the job performance of surgeons and the mediating role of job responsibility and role overload have been investigated by Jiandong et al The results of their study approve the effect of increased fatigue on the performance of surgeons and the amplification of this effect with increasing job responsibility and role overload [ 52 ]. Also in another study, Fan et al [ 32 ] stated that mental workload with increased fatigue can lead to a decrease in job performance, and fatigue mediates the relationship between mental workload and job performance.…”
Section: Discussionmentioning
confidence: 99%
“…Literature supports the idea that job stress and emotional exhaustion are predictors of various negative outcomes in employee behaviour (Karatepe & Nkendong, 2014). Another plane of work stress in work fatigue, which refers to inability to work due to physical, mental, and emotional exhaustion (Jiandong et al, 2022). Irrespective of age group, work stress exists, but yes, the impact of work stress is quite higher among older working adults in the labour market (Malik et al, n.d.).…”
Section: Work Stressmentioning
confidence: 97%
“…According to the challenge-stress hindrance model, stress refers to the extent to which individuals respond to emotional or physical stimuli from their environment. Work stress is developed among employees as a direct response to external workplace stressors such as work requirements, practice requirements, and performance appraisals (Jiandong et al, 2022). In other terms, work stress is an outcome of combining demands and controls over the job situation (Malik et al, n.d.).…”
Section: Work Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has explained a lot about the effect of a high performance system on work fatigue (Ruiz et al, 2019). In addition, it also explains the influence of the mediating effect of job responsibilities, work performance, and overtime (Jiandong et al, 2022). However, this research has limitations and gaps in the research, where many studies measure the sustainable effects of high performance systems on business results, but only a few consider the effects of total quality management practices (Peterson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%